Resistance Responses of 35 Watermelon Genotypes to Three Isolates of Fusarium oxysporum f. sp. niveum - Nazly Aswani; Suryo Wiyono; Sobir Sobir (Jurnal AgroBiogen, 2021)
Fusarium wilt caused by Fusarium oxysporum f. sp. niveum (Fon) is one of main diseases of watermelon. There have been very limited studies that tested watermelon genotypes to more than one isolates of Fon in Indonesia. This research aimed to determine the resistance of 35 watermelon genotypes to three Fon isolates taken from three different areas in Indonesia. Incubation period (IP) and disease index (DI) of the 35 watermelon genotypes were determined against three Fon isolates collected from Karawang (FK), Lampung (FL), and Purwakarta (FP). The experiment was arranged using a Completely Randomized Design with two replications. DI showed that six watermelon genotypes, i.e. New Hope, Sky Mountain, Southern Light, Super Sweet 66, Uranus, and Yellow Baby demonstrated moderate resistance to resistance phenotypes to all tested Fon isolates. IP and percentage of symptomatic plants (PSP) showed different responses among genotypes either to the same or to different isolates. Genotype New Orchid, for example, showed 57.14% symptomatic plants in less than 10 days after inoculation (DAI) when tested with FL isolate. Meanwhile, when tested with the same isolate, genotype New Dragon showed only 6.67% symptomatic plants in more than 23 DAI. The result of this study indicated that watermelon genotypes showing resistant to all tested isolates should be useful for breeding program to develop watermelon lines with broader resistance spectrum against Fon pathogen. The resistance genotypes selected should also demonstrate good agronomic performances and high yield to be considered as a new watermelon variety.